2023
DOI: 10.1017/s1049023x23006131
|View full text |Cite
|
Sign up to set email alerts
|

Anemia and Spaceflight Associated Neuro-Ocular Syndrome (SANS)

Abstract: Spaceflight associated neuro-ocular syndrome (SANS) is a collection of distinct findings seen in some astronauts following prolonged spaceflight and is characterized by: optic disc edema, globe flattening, and choroidal folds. In this manuscript, we describe the potential mechanisms linking anemia and SANS. Future research aimed at understanding the relationship between these conditions may help to develop countermeasures and mitigation efforts for SANS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…However, there is a 41-56% increase in cardiac output 17,18 , an 83% increase in straight sinus blood flow velocity 19 and an 84% increase in the middle cerebral vein flow velocity in long-term space flight 20 . More recently, chronic hemolytic anemia and a reduction in haemoglobin concentration of about 10% have been noted in long term spaceflight 21 . Whilst it has long been thought that IIH is associated with either a normal or reduced cerebral blood flow (CBF), it has also recently been shown that there are a subset of patients with IIH who have an increased CBF i.e.…”
Section: Physiology Of Sansmentioning
confidence: 99%
“…However, there is a 41-56% increase in cardiac output 17,18 , an 83% increase in straight sinus blood flow velocity 19 and an 84% increase in the middle cerebral vein flow velocity in long-term space flight 20 . More recently, chronic hemolytic anemia and a reduction in haemoglobin concentration of about 10% have been noted in long term spaceflight 21 . Whilst it has long been thought that IIH is associated with either a normal or reduced cerebral blood flow (CBF), it has also recently been shown that there are a subset of patients with IIH who have an increased CBF i.e.…”
Section: Physiology Of Sansmentioning
confidence: 99%
“…While previous case reports [5], and systematic reviews [6] have previously suggested a possible association between anaemia and IIH, this prospective study with 143 patients makes this association even more compelling, while also providing a practical recommendation to perform a complete blood count for all suspected IIH patients.SANS and IIH are both severe diseases for their different demographics, and further understanding the role of anaemia in these conditions is essential. There is a potential association between anaemia and spaceflight associated neuro-ocular syndrome (SANS) [7]. Space anaemia, refers to a decrease in the number of circulating red blood cells and plasma volume as a result of selective haemolysis that occurs during spaceflight [8].…”
mentioning
confidence: 99%
“…SANS and IIH are both severe diseases for their different demographics, and further understanding the role of anaemia in these conditions is essential. There is a potential association between anaemia and spaceflight associated neuro-ocular syndrome (SANS) [7]. Space anaemia, refers to a decrease in the number of circulating red blood cells and plasma volume as a result of selective haemolysis that occurs during spaceflight [8].…”
mentioning
confidence: 99%